Structural Behaviour Of Corrosion-Damaged Rc Short Columns Wrapped With Hybrid Fibre Reinforced Polymer Reinforcement - Basti, Emad Pournasiri (2013)
Corrosion of reinforcing steel bar in reinforced concrete (RC) structures is one of the predominant problems in civil engineering industry. Corrosion as a dangerous phenomenon could seriously affects the serviceability and durability of RC members. In order to restore the structural performance of RC structures, the repair and rehabilitation using the externally bonded Fibre Reinforced Polymer (FRP) composites is the most appropriate technique due to its advantages characteristics such as lightweight, high strength, and ease of installation without any heavy equipment.